Detective Fiction and the Ghost Story - Cook, M. author. aut Link
VIII, 231 p.
Keywords: Detective Fiction and the Ghost Story is a lively series of case studies celebrating the close relationship between detective fiction and the ghost story. It features many of the most famous authors from both genres including Conan Doyle, Agatha Christie, M. R. James and Tony Hillerman.